(3YbhO GdNjGQGJ GdeGdjI cCOGI JfTjWjI ai Shb GdChQGb GdeGdjI (B: s (3OQGSI ebGQfI (B/ s - (3eMeO MSjf YHOGdQMje MSjfs; (3Ndjd acJhQ JGOQS s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JYO YbhO GdNjGQGJ GdeGdjI (B- (3ef Cge GdJWhQGJ GdJi XgQJ ai GdCShGb GdeGdjI(B: (3h gi EMOi GdCOhGJ GdeGdjI GdeTJbI(B: (3h EMOi GHJcGQGJ GdgfOSI GdeGdjI(B: (3h JhaQ YbhO GdNjGQGJ ddeJYGedjf eRGjG eJYOOI(B: (3CgegG GdeVGQHI h GdeQGHMI; h Pdc ef NdGd GSJNOGe CehGd bdjdI GdeJGLQI ai GdShb GdeGdjI(B: (3gPG aVdG Yf GSJYeGdgG cCOGI Jbi ef eNGWQ GfNaGV CSYGQ ehLhOGJ GdeMGaX GdGSJKeGQjI (B. (3GSJgddfG GdOQGSI HaUd JegjOi Yf eGgjI h echfGJ Shb GdChQGb GdeGdjI h CgejJgG Ydi GdGbJUGO GdhWfi(B: (3h HOCfG HMKfG HGdHGH GdGhd(B: (3GdCOhGJ GdeGdjI GdMOjKI(B: (3CeG GdHGH GdKGfi abO JfGhdfG ajg JfXje YbhO GdNjGQGJ(B: (3eY JhVjM GdfXGe GdbGfhfi(B: (3h GdfXGe Gdafi(B: (3h cjajI JWHjbI ai Shb GdChQGb GdeGdjI GdeUQi h JgOa GdOQGSI Edi hVY OQGSI TGedI Yf YbhO GdNjGQGJ GdeGdjI(B: (3h JfGhdgG ef GdfGMjI GdbGfhfjI h GdafjI h cjajI JWHjbgG ai eUQ(B: (3h Pdc ai eDda hGMO(B: (3h jYO eONdG YGeG ddHGMKjf ddMUhd Ydi GdeYdheGJ GdeJYdbI HGdehVhY ef eDda hGMO(B: (3eY GdJQcjR Ydi GdYfGUQ GdCSGSjI h GdeHGOF GdegeI dJc GdYbhO(B. (3h bO JhUdfG ai fgGjI GdHMK HHYV GdfJGFL efgG Cf YbhO GdNjGQGJ GdeGdjI gi CMO YbhO GdeTJbGJ GdeGdjI GdMOjKI(B: (3h cPG GNJdGa Gdabg ai eOi eTQhYjI YbhO GdNjGQGJ GdeGdjI(B: (3h eOi JWGHbg eY GdTQjYI GdESdGejI(B: (3YOe hLhO JTQjY NGU h eSJbd HgPG GdfXGe dYbhO GdNjGQGJ GdeGdjI ai eUQ jfXe bhGYOg h UhQg(B: (3h Pdc bHd UOhQ GdbGfhf (B17 (3dSfI (B2018 (3e GdPi fU Ydi EfTGA HhQUI ddYbhO GdGLdI (B: (3h GdJi efgG YbhO GdNjGQGJ GdeGdjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2018s
(3HHdjhLQGajG(B: (3UaMGJ (B401-415s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdCShGb GdeGdjI s; (3Shb GdChQGb GdeGdjI s; (3YbhO GdNjGQGJ GdeGdjI s; (3GdGOhGJ GdeGdjg GdMOjKgs; (3HhQUg GdYbhO GdGLdgs; (3eTQhYjg YbhO GdNjGQGJs; (3GdHjY Ydi GdecThas; (3GdTQGA HGdgGeTs; (3TgGOGJ GdGjOGY GdeUQjgs; (3GdehTQGJ ai GdHhQUgs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs